Trotsky - Thatcher, Ian D. (London ; New York : Routledge, 2003)
Publisher's description: Leon Trotsky has always aroused strong passions-historians love and hate him in equal measure. This new biography provides a full account of his political life, based upon a wealth of primary sources, including previously unpublished material. Ian D. Thatcher paints a new picture of Trotsky's standing in Russian and world history. Key myths about Trotsky's heroic work as a revolutionary, especially in Russia's first revolution of 1905 and the Russian Civil War, are thrown into question. Although Trotsky had a limited understanding of crucial contemporary events such as Hitler's rise to power, he was an important thinker and politician, not least as a trenchant critic of Stalin's version of communism. This study provides a clear and accessible introduction to Trotsky's life and thought for anyone interested in twentieth-century Russian and World History.
Introduction -- Young revolutionary, 1879-1907 -- Fight for unity, 1907-14 -- War and revolution, 1914-17 -- Defending the revolution, 1917-21 -- Revolution in decline, 1921-4 -- Opposition and defeat, 1925-9 -- Against Stalinism and fascism, 1929-33 -- Final exile : the Fourth International and world events, 1933-40 -- Conclusion.
Includes bibliographical references (pages 218-234) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Trotsky, Leon, -- 1879-1940.; Trotsky, Leon, -- 1879-1940; Revolutionaries -- Soviet Union -- Biography; Statesmen -- Soviet Union -- Biography; Hommes d'État -- URSS -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; Revolutionaries; Statesmen; Soviet Union; Electronic books; Biographies; Biographies; Biographies